3^10×11+6^9×120/3^9×2^4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{10.4^6.9^5+6^9.120}{8^4.3^{12}-6^{11}}=\frac{2.5.\left(2.2\right)^6.\left(3.3\right)^5+\left(2.3\right)^9.3.40}{\left(2.2.2\right)^4.3^{12}-\left(2.3\right)^{11}}=\frac{2.5.2^6.2^6.3^5.3^5+2^9.3^9.3.40}{2^4.2^4.2^4.3^{12}-2^{11}.3^{11}}\)
\(=\frac{2^{13}.5.3^{10}+2^{12}.5.3^{10}}{2^{12}.3^{12}-2^{11}.3^{11}}=\frac{2^{12}.5.3^{10}.\left(2+1\right)}{2^{11}.3^{11}\left(2.3-1\right)}=\frac{2^{12}.5.3^{11}}{2^{11}.5.3^{11}}=2\)
\(\dfrac{10.4^6.9^5+6^9.120}{8^4.3^{12}-6^{11}}=\dfrac{5.2.2^{12}.3^{10}+3^9.2^9.2^3.3.5}{2^{12}.3^{12}-2^{11}.3^{11}}\)
\(=\dfrac{5.2^{13}.3^{10}+2^{12}.3^{10}.5}{2^{11}.3^{11}\left(2.3-1\right)}=\dfrac{2^{12}.3^{10}.5\left(2+1\right)}{2^{11}.3^{11}.5}\)
\(=\dfrac{2^{11}.2.3^{10}.5.3}{2^{11}.3^{10}.3.5}=2\)